Psychic Distance and FDI: The Case of China - Vaccarini, Katiuscia (Journal of Comparative International Management)

(untitled) (Management Futures, 2015)
This paper seeks to investigate whether and to what extent psychic distance (PD) is considered by scholars as specific determinant of inbound and outbound foreign direct investments (FDI) in China. The key finding of the study is that PD as a determinant influencing FDI seems to be under-investigated. The paper also aims to systematize the limited and fragmented literature about non-tangible perceptions of “distance” between home and host economies and contributes in raising awareness on the concept of PD. It provides useful insights and practical implications for various interest groups such as international business scholars (a more comprehensive review and systematization of the concept of PD), managers (awareness raising on PD, opportunities and challenges in the IB scenario, setting up and strengthening long-term cooperation between Europe and China), and policy makers (investment flows between Europe and China, key barriers which affect companies and require action politically and institutionally to ensure that opportunities are fully exploited by companies).